Efektivitas Pendekatan Manajemen Diri pada Individu yang Mengalami Stroke - Amalia, Isna (Jurnal Kesmas Asclepius, 2025)
The study aims to assess the effectiveness of self-management carried out in post-stroke patients. This research method uses a systematic literature search from several online databases. The results of the study showed that from the five articles that have been reviewed, the level of education, health education, food intake, exercise and rehabilitation, sleep, and psychological intervention are the main factors of self-management behavior in stroke patients in the recovery stage. Self-management interventions can effectively improve the level of health education of stroke patients, help them gain confidence in self-management of the disease, and facilitate the formation of effective patient self-management behaviors, to improve the quality of life and subjective well-being of patients. In conclusion, self-management can be an alternative solution for stroke patients in improving post-stroke recovery. Self-management interventions include specific education about stroke and its effects and focus on skills training to increase active enthusiasm for patient treatment management. Keywords: Self-Management, Stroke, Treatment.